Form of Assessment in Community-based Art Learning at the Qaryah Thayyibah Learning Community (Catharsis, 2022)
Art education is creativity education, which aims as a medium to accommodate students' creative capacity. Therefore, all educational practices need to support the potential and uniqueness of students. The phenomenon in art learning is that the presence of artworks assessments is in the form of numbers made by educators in conventional schools. A humanistic assessment can support each student's potential and uniqueness. The artwork has its aesthetic value, and each individual has their perspective on work, as is the case with educational practices in the KBQT drawing class, which is considered to respect every potential and uniqueness of students through their educational practices. In its practice, the tutors' assessment of the KBQT drawing class avoids justifying student work. Therefore, the form of assessment carried out is a review, which is carried out at every meeting. This article is the result of research aimed at interpreting the form of assessment carried out in the KBQT drawing class as a form of assessment that supports the practice of humanistic education on works of art. Based on the results of the research that has been analyzed, it is stated that the form of assessment that takes place in the KBQT drawing class is not to justify student learning outcomes. However, the assessment is carried out to ensure that art learning has become a meaningful activity for the students for their real-life and future.